Emergency Arbitration in Jordanian Legislation: A Comparative Study - Abdel-Kareem Ottallah Karabsheh; Abed-Allah Hasan AL-Maslmani; Mu'taz Faris Odeh Al- Rahamneh; Urwah Ali Yousef ALalwan (International Journal of Law Research and Studies, 2026)
By studying the Jordanian Arbitration Law No. 31 of 2001, we find that the Jordanian legislator recognized emergency arbitration, but did not use the term "emergency arbitrator," which aligns with the evolving nature of arbitration cases. An emergency arbitrator provides a swift procedure for parties requiring urgent measures that cannot wait until the formation of the arbitration panel. This procedure offers a temporary solution for parties in emergency situations.The importance of the study lies in identifying the legal organization of emergency arbitration in Jordanian legislation. This helps us to understand the nature of emergency arbitration and the procedures of the emergency arbitrator, which is called pre-arbitration because of the temporary and precautionary procedures that cannot be postponed until the arbitration sessions are held in their usual form.The problem of the study focuses on identifying the extent of the binding nature of the emergency arbitrator’s decision regarding temporary and precautionary measures that require binding force, such as precautionary or provisional seizure, and the extent of application and compliance with the decision issued by the emergency arbitrator. The researcher used the descriptive, analytical, and comparative method in this study. The study concluded with a conclusion that included a set of results and recommendations, the most prominent of which was the need to amend Article 13 of the Arbitration Law of 2001, so that it more clearly defines the entity that has the authority to decide on emergency cases before holding arbitration sessions.
Keywords: Arbitration; Emergency Arbitration; Arbitrator; Provisional and Precautionary Measures; Precautionary Seizure